2008
DOI: 10.1111/j.1748-720x.2008.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

LabCorp v. Metabolite Laboratories:The Supreme Court Listens, but Declines to Speak

Abstract: In the United States, a longstanding legal rule exists against patenting natural phenomena. The Supreme Court recently had an opportunity to help define the boundaries and clarify the implications of this "natural phenomenon doctrine" in Laboratory Corporation of America v. Metabolite Labs., dismissed as improvidently granted. This article argues that the natural phenomenon doctrine renders both the patent claim at issue in LabCorp, and the patents that directly or indirectly claim biological correlations betw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
0
3
0
1
Order By: Relevance
“…Although this patent is not within the molecular diagnostics landscape as such, the outcomes of the litigation have been mooted as having significant implications for that landscape [47].…”
Section: The Us Labcorp V Metabolite Litigationmentioning
confidence: 99%
See 2 more Smart Citations
“…Although this patent is not within the molecular diagnostics landscape as such, the outcomes of the litigation have been mooted as having significant implications for that landscape [47].…”
Section: The Us Labcorp V Metabolite Litigationmentioning
confidence: 99%
“…It has also been suggested that, based on the minority judgment of the US Supreme Court and comments made by another of the Supreme Court justices when the case was being heard, the Court as a whole may well have found that claim 13 was invalid if it had been given the opportunity to do so [47]. As a consequence, this case has re-ignited the debate about the patentability of claims relating to genetic testing.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Korisno je napomenuti da se nakon objave Powersova romana odvio važan sudski spor 83 u kojem su na relevantan način ograničene mogućnosti patentiranja znanstvenih otkrića, posebice u području medicine. Dok patentiranje znanstvenih otkrića u Za prikaz sudskog procesa LabCorp v. Metabolite Laboratories koji taj specifičan slučaj stavlja u širi kontekst vidiKlein i Mahoney (2008). 83 Za jednu perspektivu o Mayo v. Prometheus sporu vidiChao (2012).…”
unclassified